Effect of astragaloside IV on cognitive dysfunction in rats with cerebrally infarcted via TGF-Î² / Smad signaling pathway - Li, Li; Guo, Yanling; Zhao, Yan’an; Wei, Jiahong; Jin, Yuanyuan (Cellular and Molecular Biology, 2020)
Cerebral infarction is an acute cerebrovascular disease caused by abnormal blood circulation in the brain. In the present study, we investigate the effect of astragaloside IV on cognitive dysfunction in cerebrally infarcted rats via transforming growth factor-Î² (TGF-Î²) / Smad signaling pathway. For this purpose, 45 rats were divided into three groups including astragaloside, model, and control. 30 of 45 healthy adult male SD rats were randomly selected to establish an acute cerebral infarction model. 15 modeled rats were enrolled as a model and astragaloside group, and another 15 rats as a blank control group. The rats in the astragaloside group were fed with astragaloside IV according to 1.08 g/kg body weight, and those in the blank group and model group were given matching normal saline. The levels of TGF-Î², Smad1, Smad3 and Smad7 of TGF-Î²/Smad signaling transduction pathway at T0 (week 0), T1 (week 3) and T2 (week 6) were determined by enzyme-linked immunosorbent assay (ELISA). The modified neurological severity score (mNSS) was used to evaluate the improvement of cognitive dysfunction in rats. The mNSS of rats with cerebral infarction in the astragaloside group was lower than that in the control group and model group (P< 0.05). While the levels of TGF-Î², Smad1, Smad3 and Smad7 in the astragaloside group were higher than those in the control group and model group (P< 0.05). Astragaloside IV plays an important role in improving cognitive dysfunction in rats with cerebral infarction while affecting the levels of TGF-Î², Smad1, Smad3 and Smad7 and activating TGF-Î² / Smad signaling pathway.